Analysis of road sprint cycling performance - Menaspa, P. (2015)
Sprint cycling ability is a key determinant of road cycling performance, with many races designed specifically for sprinters. The ability to excel in the final sprint is relevant for both individual riders and teams. Despite the importance of sprints within professional road cycling, the characteristics of professional road sprints and sprinters have yet to be extensively described. Thus, the overall objective of the five research studies contained within this doctoral thesis was to describe road cycling sprint performance and improve the general understanding of the physical, technical and tactical factors associated with such performances.